Development of a method based on thermal desorption-gas chromatography/mass spectrometry for the determination of 103 volatile organic compounds in mattresses. Issue 9 (14th July 2020) - Cao, Shurui; Wen, Yao; Xi, Cunxian; Li, Xianliang; Zhang, Lei; Wang, Guomin; Shang, Jingchuan
ABSTRACT: A sensitive and reliable method based on environment test chamber coupled with thermal desorption and gas chromatography-mass spectrometry (ETC-TD-GC/MS) was developed and validated for the determination of 103 volatile organic compounds (VOCs) emitted from mattresses. In the study, two commercial sorbent tubes were compared in terms of adsorption efficiency towards the target analytes. The result illustrated that the multisorbent tubes containing Carbopack C, Carbopack B and Carboxen 1000 had better performance than Tenax TA tubes owing to their large surface area, low capacity for water and high temperature stability, which allowed a wide range of VOCs to be absorbed, especially for VOCs with low boiling points and small molecules. To achieve the optimum conditions for the analysis, several thermal desportion parameters were accurately investigated. Under the optimal conditions, the method showed good linearities, with correlation coefficients ranging from 0.9982 to 0.9999 and the method detection limits and method quantification limitsfor target compounds in the range of 0.006 0.561 µg/m 3 and 0.020 1.870 µg/m 3, respectively. In order to evaluate the performance of the developed method on real samples, various mattresses from different manufacturers were analysed. All mattress samples were found to emit VOCs and the values of area-specific emission rate (SERs) for total target compounds were in the range of 90.25 288.63 µg/m 2 ·h. Moreover, the SERs of VOCs were influenced by the type of sponge materials and mattress fabric layers. The study demonstrated that the method is sensitive, accurate and well-suited for the determination of VOCs emitted from mattresses.